Variant analysis in Chinese families with hereditary hemorrhagic telangiectasia - Yali Zhao; Yuan Zhang; Xiangdong Wang; Luo Zhang (Molecular Genetics & Genomic Medicine, 2019)
Abstract Background Hereditary hemorrhagic telangiectasia (HHT) is a vascular dysplasia disorder characterized by epistaxis, mucocutaneous telangiectasias and arteriovenous malformations in internal organs. Recurrent epistaxis is the primary complaint in 90%‐96% of HHT patients and the other symptoms come with age. The aim of this study was to analyze HHT‐associated gene variant spectrum in Chinese HHT patients and to assess whether genetic testing could contribute to the early diagnosis. Methodology/Principal Thirty one HHT families including 62 individuals were recruited. Variants in the coding regions of four genes involved in HHT were amplified and analyzed using Sanger sequencing and multiplex ligation‐dependent probe amplification (MLPA). Results Twenty unique variants, including 8 novel variants were found in 24 of the 31 (77.4%) kindred. Diagnosis is confirmed for 7 possible individuals from 6 kindred. Thirteen ACVRL1 variants were detected from 17 isolated HHT families. Variants in ACVRL1 from 8/17 (47.1%) families were located in exon8. Seven ENG variants were found in 7 unrelated families throughout the coding region. Conclusion We conclude that ACVRL1 gene variant is 2.4 times more prevalent than that in ENG in Chinese individuals with HHT, and exon8 of the ACVRL1 gene may be a hotspot region. Genetic testing could contribute to early diagnosis for HHT.